Níveis de fibra em detergente neutro em rações para leitões na fase de creche - Nepomuceno, Rafael Carlos (2014)
Two experiments were conducted involving 120 piglets castrated males, weaned at 21 days of age. In the first experiment where used 30 animals of average weight of 7.48 ± 0.46 kg with the objective of evaluating the effects of NDF levels in diets for piglets 21-42 days old on the pH and viscosity of the gastric and intestinal contents, the concentration of short chain fatty acids in cecal contents, gastrointestinal transit time of digesta, apparent digestibility of energy and nutrients in the diets, impacts on the intestinal mucosa, weight of digestive organ, productive performance, diarrhea occurrence, composition and deposition rate nutrients and energy body. In the second experiment 90 piglets of average body weight of 6.84 ± 0.47 kg with the objective of evaluating the effects of NDF levels in diets for piglets 21-70 days old on productive performance and occurrence of diarrhea. The piglets were distributed following a randomized block design with five treatments, considering the levels of neutral detergent fiber (NDF) of 8.5; 10.5; 12.5; 14.5 and 16.5% and six replications per treatment, one animal per plot, in the first trial, and three piglets per plot in the second test, and the initial weights of the animals the criterion used for the formation of blocks. It was found that levels of NDF did not affect the pH and viscosity of the digesta in the different sections of the gastrointestinal tract, as well as the concentration of short chain fatty acids. Quadratic effect was detected for villus height in the duodenum and jejunum and crypt depth in the jejunum, with a higher level ships in diets with 12.2% NDF. Effect linear increase was observed for the weight of the stomach and cecum and cólon. It was found that NDF levels below or above 10.2 to 13.5% reduced the transit time of digesta. Quadratic effect was observed in the digestibility of all variables, as well as weight gain and feed conversion of pigs at 70 days of age. In contrast, linear effect on the occurrence of diarrhea with the increased level of NDF in the diets was observed. The increased level of NDF caused a linear increase in fat in the carcass, blood and body, while the energy in the carcass, viscera and body showed an inverse response. Quadratic effect on deposition rates of nutrients and energy in the body, with the exception of mineral matter which linear decreasing effect mediated there was na increased level of NDF (Table 5), with the best deposition rates of water, protein gross, fat, and estimated in diets with 10.3 energies; 10.3; 11.8; 8.5 and 8.6% NDF, respectively Considering the maximum animal performance is concluded that the level of NDF in diets for pigs from 21 to 70 days of age should not exceed 10%.